A Comparative Study between the Effect of Conventional Method and Improved Fertilizer Broadcaster on the Agricultural Worker Fatigue - , V. Vijaya Lakshmi, E. Shirin Hima Bindu (Archives of Current Research International, 2024)
The investigation was executed at All India Coordinated Research Project on Women in Agriculture, Post Graduate & Research Centre, PJTSAU, Hyderabad, Telangana and the experiment was conducted in Ramchandraguda village in Maheswaram mandal, Rangareddy District, Telangana State. Agricultural workers who use traditional method of fertilizer broadcasting are exposed to a variety of occupational hazards, including musculoskeletal disorders (MSDs), fatigue, and increased physiological strain. This research study investigated the physiological and ergonomic effects of using improved fertilizer broadcasters on agricultural workers. The study focused on a diverse range of crops, namely flowers, vegetables, and paddy, grown on red and black soil. A specific area of 20 x 20 square meters was designated for the research, with soil preparation involving tillage and resulting in a loose soil texture without stubbles. The sample consisted of 10 agricultural workers, with a mean age of 35 years and a work experience of approximately 4.2 years. The results of the study indicated that the improved fertilizer broadcaster is less demanding and more ergonomic than the conventional fertilizer broadcaster. Workers reported feeling less fatigued and more comfortable while using the improved fertilizer broadcaster, which could lead to improved productivity and reduced risk of injury. The drudgery index, which is a measure of worker fatigue and discomfort, was also lower when using the improved fertilizer broadcaster. This suggests that the improved fertilizer broadcaster helped to reduce the drudgery of agricultural workers. From the study it was concluded that the improved fertilizer broadcaster is a more sustainable and worker-friendly alternative to the conventional fertilizer broadcaster.